Metabolic changes and associated cytokinin signals in response to nitrate assimilation in roots and shoots of Lolium perenne - Roche, Jessica; Love, Jonathan; Guo, Qianqian; Song, Jiancheng; Cao, Mingshu; Fraser, Karl; Huege, Jan; Jones, Chris; Novák, Ondřej; Turnbull, Matthew H; Jameson, Paula E (Physiologia plantarum, 2016)
The efficiency of inorganic nitrogen (N) assimilation is a critical component of fertilizer use by plants and of forage production in Lolium perenne, an important pasture species worldwide. We present a spatiotemporal description of nitrate use efficiency in terms of metabolic responses and carbohydrate remobilization, together with components of cytokinin signal transduction following nitrate addition to N-impoverished plants. Perennial ryegrass (L. perenne cv. Grasslands Nui) plants were grown for 10 weeks in unfertilized soil and then treated with nitrate (5 mM) hydroponically. Metabolomic analysis by gas chromatography-mass spectrometry and liquid chromatography-tandem mass spectrometry revealed a dynamic interaction between N and carbon metabolism over a week-long time course represented by the relative abundance of amino acids, tricarboxylic acid intermediates and stored water-soluble carbohydrates (WSCs). The initial response to N addition was characterized by a rapid remobilization of carbon stores from the low-molecular weight WSC, along with an increase in N content and assimilation into free amino acids. Subsequently, the shoot became the main source of carbon through remobilization of a large pool of high-molecular weight WSC. Associated quantification of cytokinin levels and expression profiling of putative cytokinin response regulator genes by quantitative reverse transcription polymerase chain reaction support a role for cytokinin in the mediation of the response to N addition in perennial ryegrass. The presence of high levels of cis-zeatin-type cytokinins is discussed in the context of hormonal homeostasis under the stress of steady-state N deficiency.
Keywords: Cytokinins; průmyslová hnojiva; cytokininy; biologický transport; signální transdukce; Lolium; metabolomika; Metabolomics; uhlík; Biological Transport; Nitrates; Signal Transduction; regulátory růstu rostlin; Plant Roots; dusičnany; Carbon; kořeny rostlin; Gas Chromatography-Mass Spectrometry; hydroponie; Soil; Fertilizers; jílek; Hydroponics; Zeatin; zeatin; plynová chromatografie s hmotnostně spektrometrickou detekcí; Plant Shoots; Plant Growth Regulators; výhonky rostlin; půda